Experimental Investigation of Effect of Exhaust Gas Recirculation and Cottonseed B20 Biodiesel Fuel on Diesel Engine. (2016) - Sakhare, Nitin M.; Shelke, Pankaj S.; Lahane, Subhash
Abstract: The effect of EGR and cottonseed B20 biodiesel on engine performance, emission and combustion characteristics of a single cylinder diesel engine with power rating of 3 kW and at constant speed of 1500 rpm are studied. It is observed that ignition delay is shorter with cottonseed B20 biodiesel as compare to base diesel due to biodiesel is having higher cetane number and oxygenated fuel. It is decreased from 9.5 °CA with base diesel to 8.5 °CA with cottonseed B20 biodiesel. Premixed combustion phase is increased with cottonseed B20 biodiesel as compared base diesel whereas diffusion combustion phase is decreased. The higher premixed combustion phase is responsible for higher NOx emission. Utilization of exhaust gas recirculation (EGR) 4% and 6% by volume shows deterioration in performance of the diesel engine. This was the main reason to use small quantity (4% and 6% by volume) of EGR only to reduce NOx. NOx emission increased with cottonseed B20 biodiesel whereas the emission decreased with exhaust gas recirculation. CO and HC emission decreased with cottonseed B20 biodiesel due to zero aromatic, oxygenated fuel results in clean burning of fuel. However, CO and HC emissions slightly increased with exhaust gas recirculation.